Kontekstualisasi Pendidikan Agama Islam terhadap Pendidikan Anti Korupsi: Penelitian - Nurhanudin; Widodo Winarso; Cecep Sumarna (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Corruption is a serious problem that is rooted in various sectors of life, including education. One strategic approach to preventing corruption from an early age is through education, especially Islamic Religious Education (PAI). This article aims to examine how the values ​​in PAI can be contextualized effectively in anti-corruption education. Using a qualitative-descriptive approach and literature review, this article explores Islamic ethical principles such as honesty (ṣidq), trust, responsibility and justice as core values ​​in building anti-corruption character. The findings show that the integration of PAI values ​​into the curriculum and educational practices can shape students' moral awareness and integrity behavior on an ongoing basis. This contextualization emphasizes that anti-corruption education is not only limited to legal knowledge, but also spiritual and moral strengthening that originates from Islamic teachings. Thus, PAI has a strategic role in forming a generation with character, integrity and commitment to eradicating corruption